Needs Analysis of Assessment Instruments to Measure Mathematical Communication Skills of Phase D Students in Measurement Content - W. Eggy Yufentya; Elfis Suanto; Maimunah Maimunah (Department of Mathematics Education Program IPI Garut, 2025)
Asesmen dalam pembelajaran matematika harus dapat mengukur kemampuan matematis yang diharapkan dimiliki peserta didik, salah satunya yaitu kemampuan komunikasi matematis. Namun bentuk penilaian yang ada saat ini cenderung berfokus pada penilaian kompetensi kognitif peserta didik dan mengabaikan dimensi penting lain dari pembelajaran. Tujuan penelitian ini adalah untuk menganalisis kebutuhan dalam mengembangkan instrumen asesmen untuk mengukur kemampuan komunikasi matematis peserta didik fase D pada konten pengukuran. Penelitian ini merupakan penelitian pengembangan awal dengan metode mengadopsi langkah define pada model pengembangan 4D. Subjek penelitian ini adalah 20 orang guru matematika dan 15 orang peserta didik SMP di Pekanbaru. Instrumen penelitian yang digunakan adalah penyebaran angket kepada guru dan pemberian soal pada peserta didik. Hasil yang diperoleh pada penelitian ini menunjukkan bahwa diperlukan adanya pengembangan instrumen asesmen yang dapat mengukur kemampuan komunikasi matematis peserta didik fase D pada konten pengukuran. Assessment in mathematics learning should be able to measure the mathematical abilities that students are expected to possess, one of which is mathematical communication skills. Nevertheless, the prevailing forms of assessment tend to focus primarily on evaluating students’ cognitive competencies, while overlooking other important dimensions of learning. The purpose of this study is to analyze the needs in developing assessment instruments to measure students’ mathematical communication skills of Phase D in the context of measurement. This research is kind of preliminary development research and the method adopts the define stage of the 4D development model. The research subjects consisted of 20 mathematics teachers and 15 junior high school students in Pekanbaru. The research instruments used were teacher questionnaires and test items to students. The results of this study indicate the necessity of developing assessment instruments that are able to measure the mathematical communication skills of Phase D students in measurement content.